Intermittent Administration of Parathyroid Hormone Enhances Odonto/Osteogenic Differentiation of Stem Cells from the Apical Papilla via JNK and P38 MAPK Pathways - Xiyao Pang; Ying Zhuang; Zehan Li; Shuanglin Jing; Qin Cai; Fengge Zhang; Changao Xue; Jinhua Yu (Stem Cells International)
Objective. Parathyroid hormone (PTH) is considered to be essential during the tooth development. Stem cells from the apical papilla (SCAPs) are responsible for dentine formation. However, the interaction between PTH and SCAPs remains unclear. This study was aimed at investigating the effects of PTH on odonto/osteogenic differentiation capacity of SCAPs and elucidating the underlying molecular mechanisms. Materials and Methods. Here, SCAPs were isolated and identified in vitro. Effects of PTH on the proliferation of SCAPs were determined by Cell Counting Kit-8 (CCK-8), flow cytometry (FCM), and EdU. Alkaline phosphatase (ALP) activity, alizarin red staining, Western blot, and RT-PCR were carried out to detect the odonto/osteogenic differentiation of PTH-treated SCAPs as well as the participation of the MAPK signaling pathway. Results. An ALP activity assay determined that 10-8 mol/L PTH was the optimal concentration for the induction of SCAPs with no significant influence on the proliferation of SCAPs as indicated by CCK-8, FCM, and EdU. The expression of odonto/osteogenic markers was significantly upregulated in mRNA levels and protein levels. Moreover, intermittent treatment of PTH also increased phosphorylation of JNK and P38, and the differentiation was suppressed following the inhibition of JNK and P38 MAPK pathways. Conclusion. PTH can regulate the odonto/osteogenic differentiation of SCAPs via JNK and P38 MAPK pathways.